Bioaccumulation of Pb in the Gills of Perna viridis (Bivalvia: Mytilidae) in Jakarta Bay, Indonesia and its Histological Alteration - Rony Marsyal Kunda; Maman Rumanta; Leonard Raden Hutasoit (Postgraduate, University of Mataram, 2024)
Pollution in Jakarta Bay associated with terrestrial run-off and eutrophication. Bivalves have been recognized as aquatic organisms that play the most dominant role in aquatic ecosystems. Pb is an element that in many cases causes health problems in the liver, kidneys, hematopoietic system and nervous system. This study aims to analyze the bioaccumulation of Pb in the gills of P. viridis in Jakarta Bay, and its histological changes. Bioaccumulation analysis using the AAS and histology changes using transmission electron microscopy (TEM) methods. The results of AAS, showed that the value of Pb concentration in gill tissue at the two seasons did not show a noticeable difference. Pb concentrations in gills were lower at 1, 4, and 5 than at 2 and 3 stations. The results of ultrastructure analysis as an impact of Pb accumulation showed that thickening of the nucleus membrane, and a decrease in the number of microvilli. The thickening of the nucleus membrane, and the decrease in the number of microvilli are cellular responses to the entry of the Pb heavy metal into the cell. Besides, the results of this study showed inflammation, a decrease in the number of mitochondria, as well as causing cristae to be empty.